PROPOSAL OF RATIONAL EVALUATION METHODS OF STRUCTURE DAMAGE BY TSUNAMI - Yoshimichi YAMAMOTO; Nunthawath CHARUSROJTHANADECH; Kenji NARIYOSHI (My University, 2011)
In order to understand the mechanism of structure destruction by tsunami and develop rational evaluation methods of the structure damage, first, the results of tsunami damage surveys conducted in Thailand, Sri Lanka, and Japan are reported. Next, the validity of the rational evaluation method of building strength against the tsunami using Gate-type Rahmen Building Model is checked by comparing calculation results with the damage data. Then, diagrams to get pillar widths or wall thicknesses at the breaking threshold for common sizes of buildings are proposed. In addition, the evaluation of building damage in actual fields is executed by using those diagrams and a numerical simulation method of tsunami flood as verification experiments. Moreover, an evaluation method of the scour in the front of a coastal seawall by the back-flow of tsunami is also proposed.
Keywords: Seawall; Pillar; Earthquake and Tsunami Effects